Advances in Tissue Expander Technology Enable Early Targeted Intervention in Prepectoral Breast Reconstruction. Issue 8 (August 2021) - Liu, Farrah; Henn, Dominic; Shrefren, Kerry; Momeni, Arash
Abstract : Background: Seroma and infection are among the most common complications after staged prepectoral implant-based reconstruction. Advances in tissue expander technology permit seroma aspiration via an integrated drain port, thus, holding promise for improving clinical outcomes. Methods: A prospectively maintained database of patients who had undergone immediate prepectoral breast reconstruction using the Sientra AlloX2 tissue expander was used to determine the rate of postoperative seroma formation, its volume and microbiological spectrum, as well as postoperative complications. Results: 49 patients (mean age: 49 years, mean body mass index: 24.5 kg/m 2 ) underwent 79 prepectoral breast reconstructions. Seroma was clinically suspected in 26 reconstructions (32.9%) and was easily aspirated in all cases via the integrated drain port. Importantly, periprosthetic fluid was successfully aspirated in 45 reconstructions (57%) without any clinical evidence for seroma, with aspirated cumulative fluid volumes exceeding 10 cm 3 in 12 reconstructions. Bacterial cultures from aspirated fluid were positive in six patients (12.2%), of whom two developed clinical signs of infection, at which point targeted antibiotic treatment was initiated. Conclusions: Our study demonstrates that routine office-based aspiration of periprosthetic fluid via the integrated drain port of the AlloX2 tissue expander not only permits successful aspiration of periprosthetic fluid but also allows aspirated fluid to be sent for culture, thus, providing a lead-time advantage for initiation of targeted antibiotic therapy in cases of postoperative surgical site infection. Furthermore, our observations indicate that positive bacterial cultures in the absence of clinical signs of infection do not mandate antibiotic therapy.